Effect of video camera monitoring feedback on hand hygiene compliance in neonatal intensive care unit, an interventional study - SİLİ, ULUHAN; MEMİŞOĞLU, ASLI; ÖZEK, EREN; KEPENEKLİ KADAYİFCİ, EDA (My University, 2023)
Background: The purpose of this study was to determine whether use of a video camera surveillance system for hand hygiene (HH) monitoring, video-based education, and feedback could improve the HH compliance in a neonatal intensive care unit (NICU). Methods and materials: This was an interventional before-after trial conducted in a level-III NICU between July 2019 and June 2020. HH compliance was measured using randomly selected video-camera footage in the baseline, intervention, and maintenance periods. After the baseline, an intervention consisting of feedback and education with video scenarios was implemented. The primary outcome was change in HH compliance. The compliance rates were analyzed as an interrupted time series (ITS) with a segmented regression model adjusted for autocorrelation for each study period. Results: We identified a total of 8335 HH indications. There were non significant increases in the total compliance rate (9.0%, 95% CI -2% to 20%) at the time of intervention and in the compliance rate after intervention (0.26%, 95% CI -0.31% to 0.84%) per day. The hand hygiene compliance before patient contact significantly increased (19.8%, 95% CI, 4.8%-34.8%). Incorrect glove use improved non-significantly with the intervention (-3.4%, 95% CI -13.4% to 6.7%). Conclusion: In this study of HH monitoring using video-camera footage combined with an intervention including feedback and education, there were inconsistent improvements in HH compliance. However, these improvements were not sustained in the long term. Frequent feedback and education may be required to sustain high compliance.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Klinik Tıp; İmmünoloji; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; BULAŞICI HASTALIKLAR; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Life Sciences (LIFE); Social Sciences (SOC); CLINICAL MEDICINE; IMMUNOLOGY; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; INFECTIOUS DISEASES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Epidemiyoloji; Sağlık Politikaları; Halk, Çevre ve İş Sağlığı; Bulaşıcı hastalıklar; Epidemiology; Health Policy; Public Health, Environmental and Occupational Health; Infectious Diseases; Glove use; Hawthorne effect; Hospital acquired infections; Video camera footage; Video camera footage; Glove use; Hawthorne effect; Hospital acquired infections